Kajian Ketersediaan Bahan Baku, Tingkat Persaingan, dan Perilaku Kewirausahaan dalam Mendukung Perkembangan Usaha - Anugrah Putra Perdana; Muhammad Dinar; Muhammad Hasan; Rahmatullah; M. Ihsan Said Ahmad (Journal of Economic Education and Entrepreneurship Studies, 2020)
This study aims to determine the availability of raw materials, the level of competition, and entrepreneurial behavior of the furniture business in Manggala District, Makassar City in supporting business development. This research is categorized as a descriptive study with a qualitative approach, data collection is done using the method of observation, interviews, and documentation. The analysis technique used is the SWOT analysis. The results of this study indicate that furniture business owners in Manggala District, Makassar City have 4 indicators of raw material availability, namely: estimated usage, material prices, inventory costs, and waiting time. And the level of competition has 6 indicators, namely: price, quality, customer loyalty, discounted prices, marketing techniques, target market. As well as entrepreneurial behavior has 4 indicators, namely: obstacles, risks, innovation, cooperation, where the results of the SWOT analysis that have been carried out, there are four strategic choices for furniture business in Manggala District, Makassar City, consisting of strengths opportunities (SO), weakness opportunities (WO). ), Strength threats (ST), and weakness threats (WT).